Hybrid Texts, Assembled Bodies: Michel Gondry's Merging of Camera and Dancer in "Let Forever Be" - Addie Tsai (The International Journal of Screendance, 2016)
Michel Gondry, a filmmaker who created and directed music videos for Propaganda Films, which produced close to a third of all music videos by 1990, began his career in music video and film during this time, where he experimented with collaging postmodern and commercial filmmaking. In 1936, cultural critic and German philosopher Walter Benjamin argued that art fundamentally changes in the age of mechanical reproduction, creating questions of authenticity and aura. This article argues that Gondry’s video “Let Forever Be,” for The Chemical Brothers, illustrates Benjamin’s argument not only in that the digital video itself artificially reproduces the bodies embedded within it, but also in Gondry’s employment of collage, special effects, and camera-enabled illusions in order to create a simulated and dream-like world.
Keywords: Michel Gondry; music video; Busby Berkeley; Walter Benjamin; simulacra